2006
DOI: 10.1111/j.1541-4329.2005.tb00064.x
|View full text |Cite
|
Sign up to set email alerts
|

Food Safety and Regulation: Evaluation of an Online Multimedia Course

Abstract: The effectiveness of, and student attitudes toward, an online Food Safety and Regulation course (WEB) were compared with lecture (LECTURE) and combined lecture/online (COMBINED) courses. All students took identical pre‐tests, post‐tests, and attitude assessments. No significant differences were detected in pre‐test scores. Post‐test results for WEB, LECTURE, and COMBINED groups were 65.9±3.02, 67.1±2.62, and 73.5±2.59 (mean±SEM), respectively. After controlling for the pretest, the COMBINED score was significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…More than 50% of students who received both the lecture and access to the Facebook page indicated that they learned more from the Facebook page than from the lecture. Findings related to the comparison between the social media-based intervention and a food safety lecture are consistent with research suggesting that online food safety education is as effective as lecture and other traditional methods of education (2, 15,19).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…More than 50% of students who received both the lecture and access to the Facebook page indicated that they learned more from the Facebook page than from the lecture. Findings related to the comparison between the social media-based intervention and a food safety lecture are consistent with research suggesting that online food safety education is as effective as lecture and other traditional methods of education (2, 15,19).…”
Section: Discussionsupporting
confidence: 77%
“…Computer-based training is as effective as lecturing for improving knowledge and attitudes related to food safety (2). Online learning environments can broaden learning opportunities because of the independent, self-paced, and flexible nature of these environments (15). Researchers found that a Web-based food safety and reg ulation course for college students was as effective as a comparable lecture-based course.…”
mentioning
confidence: 99%
“…A modified randomized pretest/posttest control group design (Figure 3) was used in this study. Pintauro and others (2005) recently implemented a similar experimental design to compare the knowledge gain and attitudes of students using 3 instructional methods. Four United States Dept.…”
Section: Methodsmentioning
confidence: 99%
“…Computer‐based training in FS for food handlers has been shown to be as effective as face‐to‐face instruction in improving knowledge and attitudes about FS (Fenton and others 2006) and easier to implement (Costello and others 1997). Web‐based college‐level FS instruction was shown to be as effective as lecture to improve FS knowledge (Pintauro and others 2005). Teachers can use the Internet to communicate or collaborate with peers, keep current on research, and access classroom resources.…”
Section: Introductionmentioning
confidence: 99%